MRI study of hydrophilic xanthan tablets with incorporated model drug - Mikac, Urša; Baumgartner, Saša; Sepe, Ana; Kristl, Julijana (Diffusion Fundamentals, 2013)
Magnetic resonance imaging was used to study swelling dynamics and hydrogel formation of xanthan tablets with or without Pentoxifylline drug in water and HCl pH 1.2 media at two different ionic strengths. Significant changes were observed only in the erosion front positions leading to different hydrogel thicknesses. The impact of the drug on the hydrogel thickness was found to be dependent on the medium conditions at high enough drug amount. The drug does not change the hydrogel thickness in water medium, whereas in acid medium the presence of the drug results in thinner hydrogel. The increased ionic strength in water medium also leads to formation of the thinner hydrogel layer in tablets with high enough drug content, while the effect of NaCl in HCl pH 1.2 medium is very small.